2012
DOI: 10.1590/s0102-09352012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma rico em plaquetas no tratamento de lesões condrais articulares induzidas experimentalmente em equinos: avaliação clínica, macroscópica, histológica e histoquímica

Abstract: Plasma rico em plaquetas no tratamento de lesões condrais articulares induzidas experimentalmente em equinos: avaliação clínica, macroscópica, histológica e histoquímica [Platelet-rich plasma RESUMOEstudou-se a eficácia do plasma rico em plaquetas (PRP) no tratamento de lesões condrais articulares, experimentalmente induzidas em equinos. Para isso, foi induzida uma lesão condral, na tróclea medial femoral dos dois membros pélvicos de quatro animais. Após 30 dias da indução, as oito articulações foram dividi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 23 publications
1
14
0
15
Order By: Relevance
“…The sample size used in this study was set because of bioethical issues and to ensure that the number of animals included would provide reliable and valid scientific results in terms of statistical significance. In addition, previous work performed and published by the researchers corroborates the use of smaller sample sizes, as planned in this study 1,8,12,14,15 .…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The sample size used in this study was set because of bioethical issues and to ensure that the number of animals included would provide reliable and valid scientific results in terms of statistical significance. In addition, previous work performed and published by the researchers corroborates the use of smaller sample sizes, as planned in this study 1,8,12,14,15 .…”
Section: Methodssupporting
confidence: 84%
“…Complete re-epithelialization was already present in all wounds treated with PRP, similar to the description in the study by Bauer et al 27 However, at M17, the microscopic analysis of samples from the treated group revealed the presence of inflammatory cells consistent with the initial phase (inflammatory) of healing 19 . Similarly, on the basis of an analysis of synovial fluid, Yamada et al 14 concluded that treatment of joint lesions with PRP did not significantly minimize the degree of inflammation compared to saline solution. We agree with the authors that it is most likely that, despite the anti-inflammatory effects of PRP in some studies 15,27 , de-granulated platelets in tissue lesions may activate chemical mediators such as cytokines, and therefore, may alter the inflammatory response during tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…No PRP utilizado nesse trabalho foi desprezada a zona de névoa. A retirada da fração que contém os leucócitos diminui a possibilidade de reações inflamatórias adversas, a produção exacerbada de citocinas próin-flamatórias e o acentuado influxo celular (Yamada et al 2012).…”
Section: Discussionunclassified
“…O tempo de permanência desse arcabouço de PRP, formado pelo gel de fibrina, é variável segundo a literatura, podendo durar de 7 a 15 dias (Yamada 2011, Xie et al 2014. Ainda, o arcabouço de PRP possui vantagens como: a fácil obtenção, simples aplicação e pouco custo de produção (Yamada et al 2012), favorecendo o retorno biomecânico da articulação comprometida e reduzindo a dor (Kon et al 2010, Sun et al 2010, Yamada 2011, Milano et al 2010, Xie et al 2012, Lee et al 2013.…”
Section: Introductionunclassified
“…O plasma rico em plaquetas (PRP) é uma alternativa de biomaterial, rico em plaquetas e consequentemente em fatores de crescimento plaquetário (FCP), que, quando aplicado diretamente sobre o foco da fratura, além de acelerar o processo de cicatrização, promove a orientação e a adesão de células-tronco mesenquimais responsáveis pelo processo de consolidação e reparação tecidual (Maia et al, 2009;Sánchez et al, 2009;Carmona et al, 2007;Yamada et al, 2012).…”
Section: Introductionunclassified